Unraveling the insomnia puzzle: sleep reactivity, attention deficit hyperactivity symptoms, and insomnia severity in ADHD Patients - Hilal Uygur (Frontiers in Psychiatry)
IntroductionInsomnia is the most common sleep problem among adults with attention deficit hyperactivity disorder (ADHD). The severity of insomnia can exacerbate the symptoms of ADHD. Identifying the predictive factors that contribute to insomnia severity may be crucial in treating insomnia among adults with ADHD. One potential factor contributing to insomnia is sleep reactivity, which refers to the tendency to experience insomnia triggered by stress. This phenomenon, also known as vulnerability to stress-related insomnia, reflects the extent to which individuals are prone to developing insomnia in response to stressful situations. To date, sleep reactivity in adults with ADHD has not been studied. This study aimed to investigate the relationship between sleep reactivity, attention deficit hyperactivity symptoms, and the severity of insomnia in adults with ADHD.MethodsThis study included 61 adults with ADHD with no comorbid psychiatric or medical diseases and 61 adult healthy controls (HCs) matched for age, sex, body mass index, and years of education. All participants completed the sociodemographic data form, Ford Insomnia Response to Stress Test (FIRST), Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), Adult ADHD Self-Report Scale (ASRS), and Wender Utah Rating Scale (WURS).ResultsSleep reactivity, insomnia severity, and poor sleep quality were higher in adults with ADHD compared to HCs. Higher sleep reactivity was associated with worse sleep outcomes in both groups, whereas higher sleep reactivity was associated with severe ADHD symptoms in the HCs group. In the ADHD group, insomnia severity was predicted by higher sleep reactivity, ASRS, and being female (R2 = 0.32, F (6, 61) = 4.36, p = 0.001), not age, ADHD medication use, and WURS.ConclusionOur findings suggest that higher sleep reactivity, increased ADHD symptoms, and being female may predict the severity of insomnia in adults with ADHD.